## Question 2. Check whether the value given in the brackets is a solution to the given equation or not.

**(a)** n + 5 = 19 (n = 1)**(b)** 7n + 5 = 19 (n = – 2)**(c)** 7n + 5 = 19 (n = 2)**(d)** 4p – 3 = 13 (p = 1)**(e)** 4p – 3 = 13 (p = – 4)**(f)** 4p – 3 = 13 (p = 0).

**Answer:**

**(a) n + 5 = 19 (n = 1)**

L.H.S. = n + 5 = 1 + 5 | when n = 1 = 5

R.H.S. = 19

∵ L.H.S. ≠ R.H.S.

∴ n = 1 is not a solution to the given equation n + 5 = 19.

**(b) 7n + 5 = 19 (n = – 2)**

L.H.S. = 7n + 5 = 7(- 2) + 5 | when n = – 2 = – 14 + 5 = – 9

R.H.S. = 19

∵ L.H.S. ≠ R.H.S.

∴ n = – 2 is not a solution to the given equation 7n + 5 = 19.

**(c) 7n + 5 = 19 (n = 2)**

L.H.S. = In + 5 = 7(2) + 5 | when n = 2 = 14 + 5 = 19 = R.H.S.

∴ n = 2 is a solution to the given equation 7n + 5 = 19.

**(d) 4p – 3 = 13 (p = 1)**

L.H.S. = 4p – 3 = 4(1) – 3 | when p = 1 = 4 – 3 = 1

R.H.S. = 13

∵ L.H.S. ≠ R.H.S.

∴ p = 1 is not a solution to the given equation 4p – 3 = 13.

**(e) 4p – 3 = 13 (p = – 4)**

L.H.S. = 4p – 3 = 4(- 4) – 3 , | when p = – 4 = – 16 – 3 = – 19

R.H.S. = 13

∵ L.H.S. ≠ R.H.S.

∴ p = – 4 is not a solution to the given equation

4p – 3 = 13.

**(f) 4p – 3 = 13 (p = 0)**

L.H.S. = 4 (p) – 3 = 4(0) – 3 | when p = 0 = 0 – 3 = – 3

R.H.S. = 13

∵ L.H.S. ≠ R.H.S.

∴ p = 0 is not a solution to the given equation 4p – 3 = 13.